Comparative biodiversity of animals in rural and urban habitats (Zoological Records and Reviews, 2023)
Urbanisation is one of the most rapid and ecologically disruptive land-use changes globally, transforming natural andagricultural habitats into built environments with profound consequences for animal biodiversity. Yet the urban-ruralgradient is not uniformly impoverishing for all taxonomic groups: some generalist species thrive in urban environments,while specialist taxa are eliminated, resulting in the well-documented pattern of biotic homogenisation across urbanisinglandscapes. This study presents a quantitative multi-taxon comparison of animal biodiversity across a fully replicatedrural-urban gradient in and around Hyderabad, India -- one of South Asia's fastest-growing megacities -- encompassingbirds, butterflies, small mammals, herpetofauna, and ground beetles (Carabidae) at 54 sites surveyed using standardisedprotocols over two years (2020-2022). A total of 584 animal species were documented across five groups. Total speciesrichness declined significantly with increasing urbanisation intensity for all groups except birds, which showed anon-linear response with highest richness at intermediate (suburban) urbanisation. Beta-diversity declined sharply alongthe gradient, confirming biotic homogenisation. Impervious surface cover, green space proportion, and tree canopy coverare the three strongest predictors of total animal species richness. Urban green spaces -- parks, gardens, and urbanforest patches -- support significantly higher biodiversity than built-up matrices and serve as critical refugia forurban-sensitive species. Conservation and urban planning recommendations for biodiversity-sensitive urbandevelopment in South Asian megacities are presented.